A Single Case Study of Transpersonal Dynamics among a Working University Student Following the Death of His Father - Najwa Aurellia Putri; Sabti Riguna Hidayah; Fatimah Azzakiyah; Aida Ad’ha; Birgita Intan Sherlyna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to explore the dynamics of transpersonal experiences among a working university student following the death of his father, encompassing alcohol consumption as a form of emotional escape, religious disengagement, and recovery through non-coercive spiritual companionship. The study employed a qualitative approach using a single-case study design. The participant was